Urban Poverty: A Study of Income Patterns and Processes of the Poor Families in Kathmandu - Dahal, Kedar (Banking Journal, 2011)
The poor are highly migrate from the surrounding districts of Kathmandu valley and largely dependent on direct cash income from the informal activities. Casual wage labor, petty trade and private and professional services are common livelihood activities. However, availability of income generation activities remains largely irregular and depends on the season, gender, age of person, ethnic and education background. Foreign employment, skill-based activities and petty trade fetch the highest return. It is also found that the level of family income is determined not only by ethnic background; but there are other factors, for example family structure, working hours, nature of work and seasonality. There is a significant impact of education and working hour in household income. Poor are assets of urban economy. We could not neglect them. They are hard working and decent people. But poor policy and attitude makes them highly vulnerable in the urban environment. However, all people living in the squatter or slum are not only poor but some of them are economically well-off, though they have poor accessed of modern banking and financial institutions, in many cases, banking policies discouraged them for providing credit facilities. Key Words: Poverty Pockets; Communities; Urban; Livelihood DOI: http://dx.doi.org/10.3126/bj.v1i1.5142 Banking Journal Vol.1(1) 2011: 29-45